Development of "hand magic" educational media to introduce the concept of numbers for young learners - Nuraina, Nuraina; Sari, Dwhy Dinda; Yusra, Yusra; Yasmin, Aina (Aṭfālunā Journal of Islamic Early Childhood Education, 2023)
Introducing the concept of numbers is important from an early age because it is the basis of mathematics, which consists of counting, mentioning objects with numbers, connecting objects with numbers, comparing, recognizing, and writing numbers. This research aims to develop educational game tools to introduce the concept of numbers in children aged 4-5 years. This type of research and development (R&D) uses the 4-D development model, which consists of defining, designing, developing, and disseminating. Data was collected by using observation and questionnaires. Data were analyzed from the results of questionnaires distributed to expert validators to assess the media developed, as well as the results of observations of children's number concept abilities during the field test. The results showed that the educational media developed and named "hand magic" had very feasible criteria for use with the acquisition of a media design validation score of 3.8%, early childhood expert validation of 3.9%, and validation from early childhood teachers of 3.9%. The results of trial observations for small groups were 44% with Developing as Expected (DE) criteria, 56% with Developing Very Well (DW) criteria, and for large groups obtained a value of 18.6% with Starting to Develop (SD) criteria, 47.9% with DE criteria, and 29.3% with DW criteria. Therefore, hand magic media has contributed to helping young learner teachers introduce number concepts in early childhood. More research topics are suggested, along with some challenges of utilizing a play method with the hand magic educational game in the classroom.